What influence Customer Patronage of Insurance Policies: An Empirical Assessment of Socio-Economic and Demographic Determinants of Insurance Patronage in Ghana - Fofie, Gloria A. (International Review of Management and Marketing, 2016)
The study attempts to explore and assess the social, economic and demographic factors that are likely to influence the patronage of insurance in Ghana. Employing a cross-sectional and convenient sampling method, 200 respondents were selected to answer semi-structured questionnaires. Using a Probit econometric regression model for analysis, the results indicate these socio-economic and demographic determinants are positively and significantly related to insurance demand, except that of religion. This implies that socio-economic and demographic determinants with the exception of religion play major roles in influencing people’s decision to subscribe to insurance policies. Again, it was observed that with the exception of religion, all the socioeconomic and demographic variables have strong positive relationship with insurance patronage in Ghana. Apart from income which was identified as the major challenge to subscribing to insurance policies, other challenges such as lack of knowledge on insurance policies, inadequate transparency of insurance policies, and difficulty in obtaining insurance claims, do deter people from taking up insurance policies. Based on these outcomes and challenges, the study recommends that insurance companies develop marketing strategies that are customer centered, by taking into consideration the socioeconomic and demographic characteristics of consumers. Keywords: Customer Patronage, Perceived Enjoyment, Customer Satisfaction, Insurance Policies, Insurance Subscriber. JEL Classification: N3